Penerapan Model Problem Based Learning untuk Meningkatkan Motivasi Belajar Siswa - Ni Kadek Erina Susanti; Mega Suci Yati; Baiq Niswatul Khair (Journal of Science Instruction and Technology, 2023)
Identifying learning models that influence student learning motivation has generally received less attention. This leads to their low motivation to learn. The purpose of this study is to enhance students' learning motivation through the application of problem-based learning teaching model. This type of study is a classroom study that is conducted in two stages. The stages of each cycle include planning, action, observation and reflection. The subjects of the study were IVA class SDN 7 Chakranegara students in the academic year 2022/2023. The instrument of this study is the Learning Motivation Questionnaire, which is valid and reliable. The results of this study showed that students' learning motivation increased in each cycle from 49.810% in the pre-cycle, then from 57.259% in Cycle I and 78.074% in Cycle II. Based on the results of this study, it can be concluded that the application of problem-based learning teaching model can enhance students' learning motivation.